2006
DOI: 10.1016/j.jpain.2006.01.442
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in a Couples Context: A Review and Integration of Theoretical Models and Empirical Evidence

Abstract: Researchers have become increasingly interested in the social context of chronic pain conditions. The purpose of this article is to provide an integrated review of the evidence linking marital functioning with chronic pain outcomes including pain severity, physical disability, pain behaviors, and psychological distress. We first present an overview of existing models that identify an association between marital functioning and pain variables. We then review the empirical evidence for a relationship between pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
200
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(218 citation statements)
references
References 107 publications
(42 reference statements)
16
200
0
2
Order By: Relevance
“…No associations were found between solicitous and negative partner responses and sexual function, and facilitative responses were not assessed. These findings were surprising given that previous pain studies have found a significant positive relationship between solicitous and negative partner responses and disability, although a few studies failed to find an association (Leonard et al, 2006) for review). However, the vulvodynia study used single occasion, retrospective measures, which may have introduced recall biases.…”
Section: Partner Responses To Pain and Sexual Functioningmentioning
confidence: 75%
See 1 more Smart Citation
“…No associations were found between solicitous and negative partner responses and sexual function, and facilitative responses were not assessed. These findings were surprising given that previous pain studies have found a significant positive relationship between solicitous and negative partner responses and disability, although a few studies failed to find an association (Leonard et al, 2006) for review). However, the vulvodynia study used single occasion, retrospective measures, which may have introduced recall biases.…”
Section: Partner Responses To Pain and Sexual Functioningmentioning
confidence: 75%
“…There is growing evidence that interpersonal factors affect the physical health of couples 5 (Diamond, Hicks, & Otter-Henderson, 2011), and specifically that interpersonal factors increase the risk for developing and maintaining chronic pain conditions (Leonard, Cano, & Johansen, 2006). The communal coping model (CCM) of pain suggests that expressions of pain to significant others may serve to evoke particular responses, such as assistance (Sullivan et al, 2001).…”
Section: Partner Responses To Pain and Sexual Functioningmentioning
confidence: 99%
“…By contrast, patients with CMP were actually found to be more satisfied with partnership than respondents from the general population sample. Although pain may change some aspects of the relationship with one's partner and family members [28], it has no negative impact on satisfaction with these relationships. It is likely that emotional aspects such as love and affection dominate a person's feelings towards their partner and family.…”
Section: Discussionmentioning
confidence: 99%
“…The negative relationship between physical and social activity engagement and chronic pain disability is central to current theoretical models and is widely empirically supported (e.g., Leeuw et al 2007;Vlaeyen and Linton, 2012). Although, a great deal of research has been focusing on the cognitive and affective determinants of activity dis/engagement and pain disability (e.g., catastrophizing, kinesiophobia, hypervigilance), there is also accumulating evidence supporting the role of social relations on chronic pain outcomes (e.g., Krahé et al 2013;Leonard et al 2006;Hadjistavropoulos et al 2011). …”
Section: Introductionmentioning
confidence: 99%